MEMPERSIAPKAN HOMILI MULTIKULTURAL - Alphonsus Boedi Prasetijo (Lembaga Penelitian STKIP Widya Yuwana, 2017)
Preparing Multicultural Homily based on Evangelii Gaudium (The Joy of the Gospel), Pope Francis, Apostolic Exhortation on Proclamation of the Gospel in Today’s World, we could start by understanding the meaning of ‘Multicultural Homily’; preaching as a sacred dance between culture, language and meaning; facing the beauty of Homily and learning how to tell the story in homily. The power of storytelling enriched the Multicultural Homily. Pope Francis noted: On the lips of the catechist the first proclamation must ring out over and over: “Jesus Christ loves you; he gave his life to save you; and he is living at your side every day to enlighten, strengthen and free you.” (EG, no 164). Pope Francis invite us in Evangelii Gaudium “to enrich our preaching and make it more attractive” by: (1) To learn how to use images in preaching, how to appeal to imagery. (2) Use the language simplicity, clearly, directly and well-adapted. (3) The Homily is positive.